2021
DOI: 10.1530/eje-20-1301
|View full text |Cite
|
Sign up to set email alerts
|

Selective vs non-selective alpha-blockade prior to adrenalectomy for pheochromocytoma: systematic review and meta-analysis

Abstract: Objective: Alpha-adrenergic blockade is currently the first choice of preoperative treatment in patients with functional pheochromocytoma and sympathetic paraganglioma. Nevertheless, there is no consensus whether selective or non-selective alpha-blockade is superior for preventing both perioperative hemodynamic instability and complications. Design: Our study aimed to compare selective and non-selective alpha-blockade through a systematic review with meta-analysis. Methods: MEDLINE, Embase, Web of Science a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
2
13
0
1
Order By: Relevance
“…We also observed that patients receiving selective alpha-blockade required intraoperative vasodilators more frequently than those treated with non-selective alpha-blockade. Similar results were reported in a recent systematic review and meta-analysis of 1344 patients [29], describing that intraoperative vasodilators were used more frequently in the group of selective alpha-blockade (OR: 2.46, 95% CI 1.44-4.20, P = 0.001). They also found a shorter length of hospital stay (WMD: -0.58 days, 95% CI: -1.12 to -0.04, P = 0.04) in patients treated with selective-alpha blockers, maybe the shorter stay could be related to the tendency to use phenoxybenzamine in hospitalized patients and use doxazosin on an outpatient basis.…”
Section: Surgical Outcomessupporting
confidence: 88%
“…We also observed that patients receiving selective alpha-blockade required intraoperative vasodilators more frequently than those treated with non-selective alpha-blockade. Similar results were reported in a recent systematic review and meta-analysis of 1344 patients [29], describing that intraoperative vasodilators were used more frequently in the group of selective alpha-blockade (OR: 2.46, 95% CI 1.44-4.20, P = 0.001). They also found a shorter length of hospital stay (WMD: -0.58 days, 95% CI: -1.12 to -0.04, P = 0.04) in patients treated with selective-alpha blockers, maybe the shorter stay could be related to the tendency to use phenoxybenzamine in hospitalized patients and use doxazosin on an outpatient basis.…”
Section: Surgical Outcomessupporting
confidence: 88%
“…Our findings are different from Zawadzka et al . [ 25 ] where authors reported that NSAB was superior to SAB in preventing intra-operative BP fluctuations. The only similar finding is a requirement of intra-operative vasodilator drug, which was more in the SAB group.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to phenoxybenzamine, doxazosin is most prescribed due to its lower cost and worldwide availability. Nonselective α-blocker are associated with less intraoperative hypertension rates than selective agents with similar hypotension and vasopressor needs [ 47 ]. Morbimortality is similar in these 2 types of α-blockers [ 10 , 47 ].…”
Section: Preoperative Carementioning
confidence: 99%
“…Nonselective α-blocker are associated with less intraoperative hypertension rates than selective agents with similar hypotension and vasopressor needs [ 47 ]. Morbimortality is similar in these 2 types of α-blockers [ 10 , 47 ]. The α-adrenergic blocker treatment is associated with orthostatic hypotension, reflex tachycardia, dizziness, and syncope particularly when using phenoxybenzamine [ 48 , 49 ].…”
Section: Preoperative Carementioning
confidence: 99%